Estrategias de las universidades para la certificación Green Metric World University, estudios de caso en Colombia. (2021)
This research refers to the analysis of different strategies and / or measurement mechanisms based on the Green Metric World University certification, applied in Colombian universities, which serve as a starting point for observing specific cases of significant experiences, as well as the implementation of these in the University of America Foundation. This research was developed taking as reference different studies carried out in other university institutions, based on a descriptive approach, theoretical in its entirety, pointing out the most relevant cases. In this way, it was possible to establish the different guidelines and / or recommendations to apply in the FUA, seeking a high rating under Green Metric standards and thus achieve certification.